Understanding Institutions in the Context of Entrepreneurship - Kumar, Gunjan (Journal of Entrepreneurship, Business and Economics, 2014)
Purpose- Entrepreneurs propose; institutions facilitate; markets decide; knowledge grows and development occurs. This process of development with growth of knowledge through institutions and entrepreneurship may be of interest for many. But the topic „Institutions and Entrepreneurship‟ overlaps several areas of research, and therefore works are fragmented. Design/methodology/approach- The paper pulls together these various strains of research. Various theoretical and empirical studies have been discussed related to this but are of course not exhaustive. Findings- The contributions of both the classical and modern literatures are equally important in understanding the two related and valuable concepts of Institutions and Entrepreneurship. Identifying the variables through which the mechanism of Institutions affect the quantity and quality of Entrepreneurship of a region are crucial. The paper advocates the study of Institutions in a cluster; in a general framework rather than in isolation. The efficiency of an institutional set up hinges on the various complementary elements and therefore there is a need of coherence among all related variables to deliver a unified and mutually reinforcing environment. Research paper Reference to this paper should be made as follows: Kumar, G. (2014). “Understanding Institutions in the Context of Entrepreneurship”,